Beyond BCMA: the next wave of CAR T cell therapy in multiple myeloma - Miller, Kevin; Hashmi, Hamza; Rajeeve, Sridevi (Frontiers in Oncology, 2024)
Chimeric antigen receptor (CAR) T cell therapy has transformed the treatment landscape of relapsed/refractory multiple myeloma. The current Food and Drug Administration approved CAR T cell therapies idecabtagene vicleucel and ciltacabtagene autoleucel both target B cell maturation antigen (BCMA), which is expressed on the surface of malignant plasma cells. Despite deep initial responses in most patients, relapse after anti-BCMA CAR T cell therapy is common. Investigations of acquired resistance to anti-BCMA CAR T cell therapy are underway. Meanwhile, other viable antigenic targets are being pursued, including G protein-coupled receptor class C group 5 member D (GPRC5D), signaling lymphocytic activation molecule family member 7 (SLAMF7), and CD38, among others. CAR T cells targeting these antigens, alone or in combination with anti-BCMA approaches, appear to be highly promising as they move from preclinical studies to early phase clinical trials. This review summarizes the current data with novel CAR T cell targets beyond BCMA that have the potential to enter the treatment landscape in the near future.